Emerging tyrosine kinase inhibitors for head and neck cancer. (December 2013) - Bossi, Paolo; Locati, Laura; Licitra, Lisa
<x xml:space="preserve">Abstract</x> Introduction: Conventional treatments for head and neck squamous cell cancer (HNSCC) are not completely effective and present several issues in terms of toxicity. Treatments available consist of surgery, chemoradiotherapy and biological agents. Areas covered: Tyrosine-kinase inhibitors (TKIs) alone or in combination, already tested or currently under investigation, will be evaluated together with their time placement along the treatment as well as the disease setting where they were used. Expert opinion: From the results of the main trials on TKIs, it emerges that these agents added to chemotherapy in recurrent/metastatic setting do not represent the best approach because of the major side effects, worsened by the complex characteristics of treated patients, and the lack of gain in terms of efficacy. Targeted agents could better exploit their activity in other settings, such as either before local regional treatment or immediately after to modulate biological effects induced by the treatment itself (surgery and/or radiation) and/or concurrently with radiation. Future research should also focus on irreversible pan-HER inhibitors, or combination agents able to overcome primary and acquired resistance, and on relevant biomarkers that would allow for a better therapeutic index of these molecules.